Corticotroph tumor progression speed after adrenalectomy. Issue 6 (3rd November 2022) - Bessiène, Laura; Moutel, Sandrine; Lataud, Marine; Jouinot, Anne; Bonnet-Serrano, Fidéline; Guibourdenche, Jean; Villa, Chiara; Baussart, Bertrand; Gaillard, Stephan; Barat, Maxime; Dohan, Anthony; Bertagna, Xavier; et al.
Abstract: Objectives: After bilateral adrenalectomy in Cushing's disease, corticotroph tumor progression occurs in one-third to half of patients. However, progression speed is variable, ranging from slow to rapid. The aim was to explore corticotroph progression speed, its consequences and its risk factors. Design: A retrospective single-center observational study. Methods: In total, 103 patients with Cushing's disease who underwent bilateral adrenalectomy between 1990 and 2020 were included. Clinical, biological, histological and MRI features were collected. Median duration of follow-up after bilateral adrenalectomy was 9.31 years. Results: In total, 44 patients progressed (43%). Corticotroph tumor progression speed ranged from 1 to 40.7 mm per year. Progression speed was not different before and after bilateral adrenalectomy ( P = 0.29). In univariate analyses, predictive factors for rapid corticotroph tumor progression included the severity of Cushing's disease before adrenalectomy as the cause of adrenalectomy, high ACTH in the year following adrenalectomy and high Ki67 immunopositivity in the tumor. During follow-up, early morning ACTH absolute variation was associated with corticotroph tumor progression speed ( P -value = 0.001). ACTH measurement after dynamic testing did not improve this association. Conclusion: After adrenalectomy, corticotroph progression speed is highly variable and manageable with MRI and ACTH surveillance. Progression speed does not seem related to bilateral adrenalectomy but rather to intrinsic properties of highly proliferative and secreting tumors.